Using Theory to Develop Healthy Choices in Motion, a Comprehensive, Experiential Physical Activity Curriculum - Fetter, Deborah S.; Linnell, Jessica D.; Dharmar, Madan; Bergman, Jacqueline J.; Byrnes, Michele; Gerdes, Melanie A.; Ruiz, Lyndsey D.; Pang, Natalie; Pressman, Jona; Scherr, Rachel E. (Frontiers in Public Health, 2020)
Background: Research has shown that engaging in regular physical activity supports physiologic, metabolic, and immunologic processes, as well as quality of life. However, few youth in the United States meet the U.S. Department of Health and Human Services recommendation of 60 minutes of moderate-to-vigorous physical activity every day. School-based programs can be an effective avenue for engaging youth in physical activity, particularly when the design of the health education is based on theory, research, and practice. The purpose of this study was to design, implement, and evaluate a theory-driven physical activity curriculum for the Shaping Healthy Choices Program (SHCP) using a systematic approach. Methods: The experiential, inquiry-¬based physical activity curriculum, Healthy Choices in Motion (HCIM), was developed with an optional technology enhancement using Backward Design. A questionnaire to assess the curriculum’s effect on physical activity knowledge was developed and assessed for content validity, internal consistency (α=0.84), and test-retest reliability (r=0.73). The curriculum was piloted in two phases among upper elementary-aged youth: to ensure the learning goals were met (Pilot I) and to determine the curriculum’s impact on physical activity knowledge, behavior, and self-efficacy (Pilot II). Pilot II was implemented among eight 4th and 5th-grade classrooms participating in the UC CalFresh Nutrition Education Program: 1) Comparison (no intervention) (n=25); 2) SHCP only (n=22); 3) SHCP + HCIM (n=42); 4) SHCP + HCIM with technology enhancement (n=47). Analyses included unadjusted ANOVA and Bonferroni for multiple comparisons and paired t test (p<0.05). Results: Through the use of a methodical design approach, a comprehensive physical activity curriculum, called HCIM, was developed. Youth participating in HCIM improved physical activity knowledge compared to youth receiving no intervention (+2.8 points, p=0.009) and youth only in the SHCP (+3.0 points, p=0.007). Youth participating in HCIM with technology enhancement demonstrated improvements compared to youth only in the SHCP (+2.3 points, p=0.05). Conclusion: Improvements in physical activity knowledge in youth participating in HCIM may contribute to improvements in physical activity and should be further explored in conjunction with behavioral measurements.